Integration of Ensiled Corncob to Diluted Molasses as Carbon and Microbial Sources for Ethanol Production - Chongkhong, Sininart (Trends in Sciences, 2023)
To improve ethanol production, carbon and microbial sources were derived from corncob and molasses. Before investigating simultaneous saccharification and fermentation (SSF), the boiled corncob was vacuum-ensiled and the molasses was diluted. The optimal ensiling time of 4 days increased not only the amount of fermentable sugar but also the population of beneficial microorganisms. The proper dilution of molasses at a ratio of 1:3 molasses to boiled water reduced both the contamination problem and the inhibition of ethanol fermentation. The combination of the ensiled corncob and the diluted molasses could provide a substrate that is suitable for SSF without the addition of enzymes, supplements, or yeast strains. The substrate contained the optimal concentration of initial sugar (174.631 ± 0.975 g/L) and viable microorganisms (1.9×106 ± 0.1×106 CFU/mL of total bacteria and 1.0x105 ± 0.1×105CFU/mL of yeast) that could continue to hydrolyze and ferment carbohydrates in the substrate for the SSF. Using a ratio of 1:3 of ensiled corncob to diluted molasses, a pH of 4.5, and a temperature of 27 °C for 72 h, the SSF produced the highest concentration of ethanol at 93.345 ± 0.062 g/L. This work provides a cost-effective process that requires no enzyme or yeast, is simply technology, and is friendly to the environment, while the remaining solid fraction can be utilized as a suitable feedstock for biogas production. HIGHLIGHTS Vacuum-ensiling increased hydrolytic microbe activity, improving biomass hydrolysis Vacuum-ensiling increased not only sugar content but also microbe population Molasses dilution reduced contamination problem and ethanol fermentation inhibition Ensiled corncob mixed with diluted molasses was a suitable substrate for SSF SSF was completed efficiently without the addition of enzymes or yeasts GRAPHICAL ABSTRACT